Effects of Financial Soundness on Export Activities: Evidence from Firm-Level Data of Korea. Issue 3 (3rd July 2022) - Shin, Yeonjin; Hur, Jung
ABSTRACT: We examine effects of financial soundness on various export activities of manufacturing firms in South Korea. The main results are as follows. First, the export-starters prepared to have a better financial soundness a few years before becoming export-starter. Second, the better financial soundness at a given year increases a probability for a firm to become a new exporter at the following year. Third, the better financial soundness is related to covering export market entry costs rather than export continuation costs. Our findings imply that the financial soundness plays a self-selection role in increasing numbers of export firms in manufacturing sectors.